Preparation method of nano alkenyl desorption promoting agent and application of nano alkenyl desorption promoting agent in coal bed gas fracturing
By modifying graphene nanosheets and MOF materials, and using high-energy ball milling method and curing amino silicone oil, an efficient nanoalkenyl-promoting desorption agent is prepared, which solves the problems of low contact rate and limited compatibility of nanofillers in the prior art, and achieves efficient desorption of coalbed methane and the stability of desorption agents.
Patent Information
- Application Number
- CN202510335964.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the contact rate of nanofilters with coal seam rocks during coalbed methane fracturing is low, resulting in poor desorption effect and limited compatibility of various surfactants, which affects the improvement of the performance of the desorption agent.
After the graphene nanosheets and MOF materials are modified by hydrophilic and hydrophobic, they are mixed by high-energy ball milling method, and the nanoalkenyl-promoting desorption agent with high binding strength and uniformity are combined into a nanoalkenyl-promoting desorption agent with high binding strength and uniformity.
The pro-desorption effect of nanofillers on coal seam rocks is improved, the desorption effect of coal seam gas is enhanced, the mechanical strength and stability of desorption agents are improved, and the pro-desorption action time is extended.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal seam mining, and in particular relates to a preparation method of a nano-olefin-based desorption promoter and an application thereof in coal seam gas fracturing. Background Art
[0002] Coalbed methane, as a by-product resource of coal, is an unconventional natural gas formed in the coal-forming process and mainly stored in the coal reservoir in an adsorbed state. It is a new type of clean energy and high-quality chemical raw material. At present, hydraulic fracturing is the main means of coalbed methane reservoir transformation, but the characteristics of coalbed methane such as low permeability, low pressure, low saturation and heterogeneity make the effect of hydraulic fracturing vary in different regions. The most commonly used active water fracturing fluid in the coalbed methane field generally consumes a lot of water but has a low return flow rate. A large amount of clean water entering the coal seam will produce a water-sensitive effect, inhibit methane desorption, and make it difficult to produce gas in the coal reservoir. Nanofillers have a small particle size and high mechanical strength. There are a large number of capillary cracks in the cracks formed by fracturing fluid. Nanofillers can not only prevent crack collapse, increase the specific surface area and total volume of cracks, form unobstructed gas and liquid channels, but also help the return of fracturing fluid.
[0003] Patent CN118620599A discloses a method for preparing a nano-silicon-based self-infiltration desorbent and its application in coalbed methane fracturing. The coalbed methane resolution rate is improved by compounding a multi-branched surfactant, an organosilicon surfactant, and a sucrose fatty acid ester. The storage stability of the desorbent is improved by modifying the nanomaterials, which is conducive to long-term storage, increases the compatibility of the nanomaterials with the remaining components, and has better stability and temperature resistance. However, in this scheme, the contact rate of the various surfactants with the coalbed rock is low under the condition of high-pressure flowing water, the contact time is short, and they are easy to move under high pressure. The nanomaterials that are not easy to move rely on the action of a silane coupling agent to be dispersed in the desorbent, and have limited compatibility. Moreover, the desorbent obtained by mixing the three nanomaterials is affected by the mixing uniformity of the three nanomaterials, and the performance improvement of the desorbent is small. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of how to improve the desorption promoting effect of nano fillers on coal bed rocks, and to provide a preparation method of a nano olefin-based desorption promoting agent and its application in coal bed gas fracturing.
[0005] The preparation method of the present invention comprises the following steps: respectively subjecting graphene nanosheets having a large specific surface area and multiple adsorption sites and MOF materials to hydrophilic and hydrophobic modifications, mixing them by high-energy ball milling, and then compounding the polymerized graphene and the modified MOF materials by curing with amino silicone oil and isocyanate to obtain a nano-olefin-based desorption promoter with good composite uniformity and high bonding strength.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a nano-olefin-based desorption promoter comprises the following steps: Step 1: In a reaction kettle, N-vinyl pyrrolidone, 2,2,6,6-tetramethylpiperidine and benzoyl peroxide are heated to 120-130° C. under nitrogen protection for reaction for 1-2 hours to obtain a grafting agent; ethylene glycol and benzoyl peroxide are dissolved in N,N-dimethylformamide, mixed with pretreated graphene and ultrasonically dispersed to obtain a mixed dispersion; the mixed dispersion is mixed with the grafting agent, heated to 120-130° C. under nitrogen protection for reaction for 1-2 hours, filtered after cooling, the precipitate is washed, and vacuum dried to obtain polymerized graphene.
[0007] Step 2: dissolve octadecylphosphonic acid in anhydrous ethanol, add MOF material and stir to react for 20-24 hours, filter and wash the precipitate, and vacuum dry to obtain the modified MOF material.
[0008] Step 3: Disperse the modified MOF material and polymerized graphene in anhydrous ethanol, add hexamethylene diisocyanate, transfer to the grinding tank of a high-energy ball mill after ultrasonic dispersion, grind at a speed of 340-360 rpm for 16-18 hours, collect the precipitate after centrifugation, and vacuum dry at 40-50°C for 3-4 hours to obtain a nanofiller.
[0009] Step 4: dissolving the amino silicone oil in a mixed solvent, adding the nanofiller for ultrasonic dispersion, and standing for reaction for 10-20 minutes, filtering, washing the precipitate, and vacuum drying to obtain a nanoolefin-based desorption promoter.
[0010] The mixed solvent in step 4 is prepared by mixing xylene and ethyl acetate in a volume ratio of 6-7:3-4.
[0011] In step 1, the dosage ratio of N-vinyl pyrrolidone, 2,2,6,6-tetramethylpiperidine and benzoyl peroxide is 10-15 mL: 0.2-0.3 g: 0.3-0.4 g; the dosage ratio of ethylene glycol, benzoyl peroxide, N,N-dimethylformamide and pretreated graphene is 3-5 g: 1-1.5 g: 50-80 mL: 6-8 g; the dosage ratio of the mixed dispersion and the grafting agent is 50-80 mL: 1.5-2 g.
[0012] The pretreated graphene is prepared by the following steps: In a reactor, graphene oxide nanosheets, 10wt% KMnO4 solution and 25wt% NaNO3 solution are stirred evenly and then ultrasonically treated for 10-20 minutes. Concentrated sulfuric acid is slowly added to the reactor, stirred for 2-3 hours in an ice bath, heated to 200-220°C for heating reaction for 10-12 hours, filtered after cooling, the precipitate is washed, and vacuum dried to obtain pretreated graphene.
[0013] The usage ratio of graphene oxide nanosheets, KMnO4 solution, NaNO3 solution and concentrated sulfuric acid is 8-10 g: 100-120 mL: 20-30 mL: 20-25 mL.
[0014] In step 2, the usage ratio of octadecylphosphonic acid and anhydrous ethanol to neutralize the MOF material is 3-5 g: 500-700 mL: 4-5 g.
[0015] MOF materials are prepared by the following steps: In a reaction kettle, zirconium chloride, monosodium 2-sulfonate terephthalate, N,N-dimethylformamide and acetic acid are mixed and heated to 115-125° C. for reaction for 30-40 hours. After cooling, the mixture is filtered, the precipitate is washed and vacuum dried to obtain the MOF material.
[0016] The usage ratio of zirconium chloride, monosodium 2-sulfonate terephthalate, N,N-dimethylformamide and acetic acid is 5-7g:6-8g:800-900mL:100-150mL.
[0017] In step three, the usage ratio of modified MOF material, polymerized graphene, anhydrous ethanol and hexamethylene diisocyanate is 3-4 g: 3-4 g: 600-800 mL: 18-20 g.
[0018] In step 4, the dosage ratio of amino silicone oil, mixed solvent and nanofiller is 1-1.5 g: 40-50 mL: 5-6 g.
[0019] The invention discloses an application of a nano-olefin-based desorption promoter in coal-bed methane fracturing. The specific application method is as follows: the nano-olefin-based desorption promoter is compounded with potassium chloride active water to prepare a fracturing fluid.
[0020] The fracturing fluid comprises the following components by weight percentage: 1-1.5wt% of a nano-olefin-based desorption promoter, 0.8-1wt% of hexadecyltrimethylammonium bromide, 0.15-0.25wt% of sodium salicylate and 1-2wt% of potassium chloride, and the balance is water.
[0021] Beneficial effects of the present invention: (1) The nano-olefin-based desorbent promoter prepared by the present invention has hydrophilicity and hydrophobicity, and utilizes nano-fillers to promote the desorption of coal-bed methane. It has excellent mechanical strength and the ability to promote methane desorption in coal-bed methane fracturing applications. At the same time, it can improve the hydrophobicity of the surface of the coal-bed pore wall, increase the contact angle, and reduce the interfacial tension between water and the coal-bed pore wall. The nano-level nano-olefin-based desorbent promoter has strong adsorption capacity, which is helpful for the desorption of methane in the coal seam. The high mechanical strength makes the desorbent of the present invention have strong water pressure resistance in the coal seam, and the desorption promotion time is long and the effect is good; (2) The preparation method of the present invention comprises the following steps: firstly, a graphene nanosheet having a large specific surface area and multiple adsorption sites and a MOF material are subjected to hydrophilic and hydrophobic modification respectively, and then mixed by high-energy ball milling. Then, the polymerized graphene and the modified MOF material are compounded by the curing action of amino silicone oil and isocyanate to obtain a nano-olefin-based desorption promoter with good composite uniformity and high bonding strength. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1: A method for preparing a nano-olefin-based desorption promoter, comprising the following steps: Step 1: In a reactor, 8 g of graphene oxide nanosheets, 100 mL of 10 wt% KMnO4 solution and 20 mL of 25 wt% NaNO3 solution were stirred evenly and then ultrasonically treated for 10 min. 20 mL of concentrated sulfuric acid was slowly added to the reactor, stirred for 2 h in an ice bath, heated to 200 ° C and heated to react for 10 h. After cooling, the precipitate was washed with deionized water, ethanol and acetone, respectively, and vacuum dried at 80 ° C for 3 h to obtain pretreated graphene.
[0024] Step 2: In a reactor, 10 mL of N-vinyl pyrrolidone, 0.2 g of 2,2,6,6-tetramethylpiperidine and 0.3 g of benzoyl peroxide were heated to 120 ° C. under nitrogen protection for 1 h to obtain a grafting agent, 3 g of ethylene glycol and 1 g of benzoyl peroxide were dissolved in 50 mL of N, N-dimethylformamide, mixed with 6 g of pretreated graphene and ultrasonically dispersed to obtain a mixed dispersion, 50 mL of the mixed dispersion was mixed with 1.5 g of the grafting agent, heated to 120 ° C. under nitrogen protection for 1 h, filtered after cooling, washed with N, N-dimethylformamide and deionized water, and vacuum dried at 80 ° C. for 3 h to obtain polymerized graphene.
[0025] Step 3: In a reactor, 5 g of zirconium chloride, 6 g of monosodium 2-sulfonate terephthalate, 800 mL of N, N-dimethylformamide and 100 mL of acetic acid were mixed and heated to 115 ° C for 30 h. After cooling, the mixture was filtered and washed with N, N-dimethylformamide and anhydrous ethanol respectively. The mixture was vacuum dried at 80 ° C for 12 h to obtain the MOF material. 3 g of octadecylphosphonic acid was dissolved in 500 mL of anhydrous ethanol, 4 g of MOF material was added and stirred for 20 h. After filtering, the precipitate was washed with anhydrous ethanol and vacuum dried at 80 ° C for 12 h to obtain the modified MOF material.
[0026] Step 4: Disperse 3 g of modified MOF material and 3 g of polymerized graphene in 600 mL of anhydrous ethanol, add 18 g of hexamethylene diisocyanate, transfer to the grinding tank of a high-energy ball mill after ultrasonic dispersion, grind at 340 rpm for 16 h, collect the precipitate after centrifugation, and vacuum dry at 40 ° C for 3 h to obtain a nanofiller.
[0027] Step 5: Mix xylene and ethyl acetate in a volume ratio of 6:3 to obtain a mixed solvent, dissolve 1 g of amino silicone oil in 40 mL of the mixed solvent, add 5 g of nanofiller and ultrasonically disperse it, then let it react for 10 min. After filtering, wash the precipitate with ethyl acetate and anhydrous ethanol respectively, and dry it in vacuum at 40°C to obtain a nanoolefin-based desorption promoter.
[0028] The prepared nano-olefin-based desorbent promoter is formulated into a fracturing fluid, which comprises the following components by mass percentage: 1.5% of the nano-olefin-based desorbent promoter, 1% of hexadecyltrimethylammonium bromide, 0.25% of sodium salicylate and 1% of potassium chloride, and the balance is water.
[0029] Example 2: A method for preparing a nano-olefin-based desorption promoter, comprising the following steps: Step 1: In a reactor, 9 g of graphene oxide nanosheets, 110 mL of 10 wt% KMnO4 solution and 25 mL of 25 wt% NaNO3 solution were stirred evenly and then ultrasonically treated for 15 min. 22.5 mL of concentrated sulfuric acid was slowly added to the reactor, stirred for 2.5 h in an ice bath, heated to 210 ° C and heated for 11 h. After cooling, the precipitate was washed with deionized water, ethanol and acetone, respectively, and vacuum dried at 85 ° C for 3.5 h to obtain pretreated graphene.
[0030] Step 2: In a reactor, 12.5 mL of N-vinyl pyrrolidone, 0.25 g of 2,2,6,6-tetramethylpiperidine and 0.35 g of benzoyl peroxide were heated to 125 ° C. under nitrogen protection for 1.5 h to obtain a grafting agent, 4 g of ethylene glycol and 1.25 g of benzoyl peroxide were dissolved in 65 mL of N, N-dimethylformamide, mixed with 7 g of pretreated graphene and ultrasonically dispersed to obtain a mixed dispersion, 65 mL of the mixed dispersion was mixed with 1.75 g of the grafting agent, heated to 125 ° C. under nitrogen protection for 1.5 h, filtered after cooling, washed with N, N-dimethylformamide and deionized water, and vacuum dried at 85 ° C. for 3.5 h to obtain polymerized graphene.
[0031] Step 3: In a reactor, 6 g of zirconium chloride, 7 g of monosodium 2-sulfonate terephthalate, 850 mL of N, N-dimethylformamide and 125 mL of acetic acid were mixed and heated to 120 ° C for 35 h. After cooling, the mixture was filtered and washed with N, N-dimethylformamide and anhydrous ethanol respectively. The mixture was vacuum dried at 85 ° C for 14 h to obtain the MOF material. 4 g of octadecylphosphonic acid was dissolved in 600 mL of anhydrous ethanol, 4.5 g of MOF material was added and stirred for 22 h. After filtering, the precipitate was washed with anhydrous ethanol and vacuum dried at 85 ° C for 14 h to obtain the modified MOF material.
[0032] Step 4: Disperse 3.5 g of modified MOF material and 3.5 g of polymerized graphene in 700 mL of anhydrous ethanol, add 19 g of hexamethylene diisocyanate, transfer to the grinding tank of a high-energy ball mill after ultrasonic dispersion, grind at 350 rpm for 17 h, collect the precipitate after centrifugation, and vacuum dry at 45 ° C for 3.5 h to obtain a nanofiller.
[0033] Step 5: Mix xylene and ethyl acetate in a volume ratio of 6.5:3.5 to obtain a mixed solvent, dissolve 1.25 g of amino silicone oil in 45 mL of the mixed solvent, add 5.5 g of nanofiller and ultrasonically disperse it, then let it react for 15 minutes. After filtering, wash the precipitate with ethyl acetate and anhydrous ethanol respectively, and dry it in vacuum at 45°C to obtain a nanoolefin-based desorption promoter.
[0034] Example 3: A method for preparing a nano-olefin-based desorption promoter, comprising the following steps: Step 1: In a reactor, 10 g of graphene oxide nanosheets, 120 mL of 10 wt% KMnO4 solution and 30 mL of 25 wt% NaNO3 solution were stirred evenly and then ultrasonically treated for 20 min. 25 mL of concentrated sulfuric acid was slowly added to the reactor, stirred for 3 h in an ice bath, heated to 220 ° C and heated for 12 h. After cooling, the precipitate was washed with deionized water, ethanol and acetone, respectively, and vacuum dried at 90 ° C for 4 h to obtain pretreated graphene.
[0035] After the graphene oxide nanosheets are pretreated with potassium permanganate and concentrated sulfuric acid, the functional group content on the surface of the graphene oxide nanosheets is increased, which is beneficial to the grafting of the subsequent reaction of the pretreated graphene.
[0036] Step 2: In a reactor, 15 mL of N-vinyl pyrrolidone, 0.3 g of 2,2,6,6-tetramethylpiperidine and 0.4 g of benzoyl peroxide were heated to 130 ° C. under nitrogen protection for reaction for 2 h to obtain a grafting agent, 5 g of ethylene glycol and 1.5 g of benzoyl peroxide were dissolved in 80 mL of N, N-dimethylformamide, mixed with 8 g of pretreated graphene and ultrasonically dispersed to obtain a mixed dispersion, 80 mL of the mixed dispersion was mixed with 2 g of the grafting agent, heated to 130 ° C. under nitrogen protection for reaction for 2 h, filtered after cooling, washed with N, N-dimethylformamide and deionized water, and vacuum dried at 90 ° C. for 4 h to obtain polymerized graphene.
[0037] The surface of the pretreated graphene reacts with the grafting agent under the action of benzoyl peroxide, and the grafting agent is grafted on the surface of the pretreated graphene. Ethylene glycol is polymerized at one end of the grafting agent with the grafting agent as a template at high temperature to obtain a grafting agent-ethylene glycol polymer segment, which is a hydrophilic segment, so that the polymerized graphene has hydrophilicity.
[0038] Step 3: In a reactor, 7 g of zirconium chloride, 8 g of monosodium 2-sulfonate terephthalate, 900 mL of N, N-dimethylformamide and 150 mL of acetic acid were mixed and heated to 125 ° C for 40 h. After cooling, the mixture was filtered and washed with N, N-dimethylformamide and anhydrous ethanol respectively. The mixture was vacuum dried at 90 ° C for 16 h to obtain the MOF material. 5 g of octadecylphosphonic acid was dissolved in 700 mL of anhydrous ethanol, 5 g of MOF material was added and stirred for 24 h. After filtering, the precipitate was washed with anhydrous ethanol and vacuum dried at 90 ° C for 16 h to obtain the modified MOF material.
[0039] Octadecylphosphonic acid interacts with zirconium oxide clusters on the surface of the MOF material, reducing the surface free energy of the MOF material and forming a hydrophobic and lipophilic MOF material.
[0040] Step 4: Disperse 4 g of modified MOF material and 4 g of polymerized graphene in 800 mL of anhydrous ethanol, add 20 g of hexamethylene diisocyanate, transfer to the grinding tank of a high-energy ball mill after ultrasonic dispersion, grind at 360 rpm for 18 h, collect the precipitate after centrifugation, and vacuum dry at 50 ° C for 4 h to obtain a nanofiller.
[0041] Step 5: Mix xylene and ethyl acetate in a volume ratio of 7:4 to obtain a mixed solvent, dissolve 1.5 g of amino silicone oil in 50 mL of the mixed solvent, add 6 g of nanofiller and ultrasonically disperse it, then let it react for 20 min. After filtering, wash the precipitate with ethyl acetate and anhydrous ethanol respectively, and dry it in vacuum at 50°C to obtain a nanoolefin-based desorption promoter.
[0042] The modified MOF material and polymerized graphene are physically mixed by a high-energy ball milling process to form a hydrophobic-hydrophilic nanofiller, and hexamethylene diisocyanate is doped in the nanofiller. The nanofiller is mixed with amino silicone oil for reaction, and the amino silicone oil first adheres to the surface of the modified MOF material under the lipophilic effect and adsorption effect of the modified MOF material, and the amino group in the amino silicone oil undergoes a grafting reaction with the sulfonic acid group of the ligand in the modified MOF material. Then, after the amino silicone oil is adsorbed by the nano-olefin-based desorbent promoter, the hexamethylene diisocyanate in the nanofiller overflows from the pores of the nano-olefin-based desorbent promoter and undergoes a cross-linking reaction with the amino silicone oil to solidify the amino silicone oil. The polymerized graphene in the nanofiller and the modified MOF material are composited by the curing effect of the amino silicone oil, thereby improving the mechanical strength and bonding strength of the nano-olefin-based desorbent promoter to form a hydrophilic-hydrophobic nano-olefin-based desorbent promoter.
[0043] Comparative Example 1: The difference from Example 1 is that the pretreated graphene is replaced by graphene oxide nanosheets.
[0044] Comparative Example 2: The difference from Example 1 is that the nanofiller is used to replace the nano-olefin-based desorption promoter.
[0045] Comparative Example 3: The difference from Example 1 is that the modified MOF material and the polymerized graphene are replaced by graphene oxide nanosheets and MOF materials.
[0046] All solutions not specifically described in the examples and comparative examples are aqueous solutions.
[0047] The sources of some reagents in the embodiments and comparative examples are as follows: KMnO4, NaNO3, concentrated sulfuric acid, ethanol, acetic acid, acetone, N-vinylpyrrolidone, ethylene glycol, N,N-dimethylformamide, zirconium chloride, octadecylphosphonic acid, xylene, ethyl acetate, and hexamethylene diisocyanate were purchased from Sigma-Aldrich.
[0048] 2,2,6,6-Tetramethylpiperidine and benzoyl peroxide were purchased from MacLean Reagent Co., Ltd.
[0049] Graphene oxide nanosheets were purchased from Suzhou Kaifa New Material Technology Co., Ltd.
[0050] 2-Sodium sulfonate terephthalate was purchased from TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0051] Hexadecyltrimethylammonium bromide was purchased from Shanghai Shengwei Chemical Raw Materials.
[0052] The nano-olefin-based desorption promoter prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was formulated into a fracturing fluid, which included the following components by mass percentage: 1% nano-olefin-based desorption promoter, 0.8% hexadecyltrimethylammonium bromide, 0.2% sodium salicylate and 2% potassium chloride, with the remainder being water; the surface tension was measured using an interfacial tension measuring instrument in accordance with the standard GB / T6541-1986; the anti-swelling performance of the fracturing fluid was tested using an NP-01 coal rock expansion tester, and the test time was 2 hours. 16h; refer to the standard of "Method for Determination of Methane Content in Coal (High Pressure Volumetric Method)" (MT / T752-1997) to carry out isothermal adsorption methane performance test and measure the desorption amount of fracturing fluid; the coal sample is selected from the anthracite of Jiulishan Coal Mine in Jiaozuo, Henan Province. The coal sample has a methane adsorption time of 24h, an adsorption pressure of 0.5Mpa, a desorption time of 2h, a desorption pressure of 0.3Mpa, and a desorption temperature of 30°C. The control group CK is a fracturing fluid without adding nano-olefin-based desorbent. The results are shown in Table 1: Table 1 project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 CK Surface tension (mN / m) 17 16 16 19 21 22 24 Expansion rate (%) 0.049 0.046 0.045 0.051 0.053 0.055 0.058 Desorption capacity (ml / g) 1.24 1.26 1.29 1.02 0.93 0.97 0.85 It can be seen from Table 1 that the fracturing fluid prepared by the nano-olefin-based desorbent promoter of the present invention has low surface tension, can well improve the hydrophobicity of the coal sample surface, and has a low expansion rate, which reduces the expansion effect caused by the fracturing fluid soaking the coal sample, and at the same time promotes good methane desorption effect and high resolution; in Comparative Example 1, since the graphene oxide nanosheets are not pre-treated by reduction, there are fewer grafting sites between the surface and the polymer chain, and the degree of modification of the graphene oxide nanosheets is small, which reduces the hydrophilic adsorption capacity of the nano-olefin-based desorbent promoter; in Comparative Example 2, since there is no curing effect of amino silicone oil, the bonding strength of the nanofiller is not high, the polymerized graphene and the modified MOF material are dispersed, and the desorption promoting effect on the coal sample is greatly reduced; in Comparative Example 3, since the nanofiller is not hydrophobic-hydrophilic modified, the nanofiller only has the effect of increasing the specific surface area of the coal sample, and has a weak effect on improving the desorption promoting ability.
[0053] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0054] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a nano-olefin-based desorption promoter, characterized in that: The steps include: Step 1, in a reaction kettle, N-vinyl pyrrolidone, 2,2,6,6-tetramethylpiperidine and benzoyl peroxide are heated to 120-130° C. under nitrogen protection for reaction for 1-2 hours to obtain a grafting agent, ethylene glycol and benzoyl peroxide are dissolved in N,N-dimethylformamide, mixed with pretreated graphene and ultrasonically dispersed to obtain a mixed dispersion, the mixed dispersion is mixed with the grafting agent, heated to 120-130° C. under nitrogen protection for reaction for 1-2 hours, filtered after cooling, the precipitate is washed, and vacuum dried to obtain polymerized graphene; Step 2: dissolve octadecylphosphonic acid in anhydrous ethanol, add MOF material and stir to react for 20-24 hours, filter and wash the precipitate, and vacuum dry to obtain the modified MOF material; Step 3, dispersing the modified MOF material and polymerized graphene in anhydrous ethanol, adding hexamethylene diisocyanate, and transferring them to a grinding tank of a high-energy ball mill after uniform ultrasonic dispersion, grinding at a speed of 340-360 rpm for 16-18 hours, collecting the precipitate after centrifugation, and vacuum drying at 40-50° C. for 3-4 hours to obtain a nanofiller; Step 4, dissolving the amino silicone oil in a mixed solvent, adding the nanofiller for ultrasonic dispersion, and then standing to react for 10-20 minutes, filtering, washing the precipitate, and vacuum drying to obtain a nanoolefin-based desorption promoter; The mixed solvent in step 4 is prepared by mixing xylene and ethyl acetate in a volume ratio of 6-7:3-4; The usage ratio of amino silicone oil, mixed solvent and nanofiller in step 4 is 1-1.5 g: 40-50 mL: 5-6 g; The pretreated graphene described in step 1 is obtained by pretreating graphene oxide nanosheets with potassium permanganate and concentrated sulfuric acid.
2. The method for preparing a nano-olefin-based desorption promoter according to claim 1, characterized in that: In step 1, the dosage ratio of N-vinyl pyrrolidone, 2,2,6,6-tetramethylpiperidine and benzoyl peroxide is 10-15 mL: 0.2-0.3 g: 0.3-0.4 g; the dosage ratio of ethylene glycol, benzoyl peroxide, N,N-dimethylformamide and pretreated graphene is 3-5 g: 1-1.5 g: 50-80 mL: 6-8 g; the dosage ratio of the mixed dispersion and the grafting agent is 50-80 mL: 1.5-2 g.
3. The method for preparing a nano-olefin-based desorption promoter according to claim 2, wherein: The pretreated graphene is prepared by the following steps: In a reactor, graphene oxide nanosheets, 10wt% KMnO4 solution and 25wt% NaNO3 solution are stirred evenly and then ultrasonically treated for 10-20 minutes. Concentrated sulfuric acid is added to the reactor, stirred for 2-3 hours under ice bath conditions, heated to 200-220°C for heating reaction for 10-12 hours, filtered after cooling, the precipitate is washed, and vacuum dried to obtain pretreated graphene.
4. The method for preparing a nano-olefin-based desorption promoter according to claim 3, characterized in that: The usage ratio of the graphene oxide nanosheets, KMnO4 solution, NaNO3 solution and concentrated sulfuric acid is 8-10 g: 100-120 mL: 20-30 mL: 20-25 mL.
5. The method for preparing a nano-olefin-based desorption promoter according to claim 1, characterized in that: In step 2, the usage ratio of octadecylphosphonic acid and anhydrous ethanol to neutralize the MOF material is 3-5 g: 500-700 mL: 4-5 g.
6. The method for preparing a nano-olefin-based desorption promoter according to claim 5, characterized in that: The MOF material is prepared by the following steps: In a reaction kettle, zirconium chloride, monosodium 2-sulfonate terephthalate, N,N-dimethylformamide and acetic acid are mixed and heated to 115-125° C. for reaction for 30-40 hours. After cooling, the mixture is filtered, the precipitate is washed and vacuum dried to obtain the MOF material.
7. The method for preparing a nano-olefin-based desorption promoter according to claim 6, characterized in that: The usage ratio of the zirconium chloride, monosodium 2-sulfonate terephthalate, N,N-dimethylformamide and acetic acid is 5-7g: 6-8g: 800-900mL: 100-150mL.
8. The method for preparing a nano-olefin-based desorption promoter according to claim 1, characterized in that: The usage ratio of the modified MOF material, polymerized graphene, anhydrous ethanol and hexamethylene diisocyanate in step three is 3-4 g: 3-4 g: 600-800 mL: 18-20 g.
9. Application of a nano-olefin-based desorption promoter in coalbed methane fracturing, characterized in that: The specific method of the application is: compounding the nano-olefin-based desorption promoter prepared by any preparation method described in claims 1-8 with potassium chloride active water to prepare a fracturing fluid; The fracturing fluid comprises the following components by mass percentage: 1-1.5wt% of nano-olefin-based desorption promoter, 0.8-1wt% of hexadecyltrimethylammonium bromide, 0.15-0.25wt% of sodium salicylate and 1-2wt% of potassium chloride, and the balance is water.
Citation Information
Patent Citations
Multilayer structure protection plate with conductivity and preparation method thereof
CN116476489A
Micro-nano polymerized graphene blocking agent and preparation method thereof
CN116875286A
Conductive agent for plastic and preparation method thereof
CN117903557A
Preparation method of nanometer silicon-based self-imbibition and desorption agent and application of nanometer silicon-based self-imbibition and desorption agent in coal bed gas fracturing
CN118620599A
Cited By
Resolution-promoting permeation enhancer and preparation method thereof
CN121628606A
Preparation method of environment-friendly nano alkenyl gas discharge aiding agent and application of environment-friendly nano alkenyl gas discharge aiding agent in coal mine discharge and mining
CN122213963A